Problematika Hukum Calon Tunggal dalam Pemilihan Kepala Daerah Serentak Tahun 2015 - Maryam Nur Hidayati (Universitas Islam Indonesia, 2016)
The legal issue on the single candidate of regional head has been initiated with the emergence of phenomenon of the single candidate of regional head in a number of regions in Indonesia. In reality, Law Number 8 of 2015 does not anticipate the existence of the candidate of regional head and to anticipate such condition, the Regulation of KPU No. 12 of 2015 regarding the postpone of the election of regional head is issued if there is only one pair of condidate in one region. The research studies the issues: first, the legal issue the single candidate of regional head in the election of the regional head is contemporaneous in 2015 in accordance with Regulation No. 8 of 2015; Second, the effort to cope with the single candidate of regional head in the following election of regional head. This is a qualitative research with the method of normative-descriptive approach that has been analyzed descriptively and processed using the literatures from the secondary data sources. The results of the research showed that first, the legal issue on the single candidate of regional head in the election of the regional head simultaneously occurred in 2015 is initiated with the legal solution from KPU with the issue of Regulation of KPU no. 12 of 2015 and the existence of the legal claim of judicial review to the Constitutional Court creating a number of legal implications. Second, the effort to prepare the next contemporaneous election of the regional head needs to be given a revision of Regulation No. 8 of 2015. This is as an effort to enforce the demoracy and to prioritize the people’s rights in Indonesia. Keywords: Legal issues, single candidate, election of regional head